Guidelines for Teacher Counseling in School - Sitthisawasdiwut, Kamonlak (Legal State Journal, 2023)
This academic article aims to analyze counseling for a school counseling approach to teachers who need to give advice to students so that students can make decisions and choose solutions for their own problems, change desirable behaviors and live happily in society. In addition, teachers can advise students effectively and achieve their objectives. Teachers must have knowledge, ability and good characteristics to be counselors. Teachers should have knowledge in counseling psychology and counseling theory to be used in counseling students, received training in counseling to have expertise and skills in counseling which will affect the counselor to receive help and find solutions to problems. Including the mentor teacher must have a good attitude towards being a mentor. A good attitude is the satisfaction of helping students solve problems, lead creative lives and live in society. Therefore, the importance of counseling in schools in order to help students develop desired behavior. It is very important that government agencies and private organizations should work together to support teachers with the knowledge and ability to give counseling to help prevent, Correct, and develop the behavior of students, who are the nation’s youth, to have desirable behavior to continue to be the strength of the nation.